A multifunctional nanocellulose-based hydrogel for strain sensing and self-powering applications. (15th September 2021) - Wang, Baobin; Dai, Lin; Hunter, Lauren Alyssa; Zhang, Lei; Yang, Guihua; Chen, Jiachuan; Zhang, Xingye; He, Zhibin; Ni, Yonghao
Abstract: Ionic conductive hydrogel with multifunctional properties have shown promising application potential in various fields, including electronic skin, wearable devices and sensors. Herein, a highly stretchable (up to 2800% strain), tough, adhesive ionic conductive hydrogel are prepared using cationic nanocellulose (CCNC) to disperse/stabilize graphitic carbon nitride (g-C3 N4 ), forming CCNC-g-C3 N4 complexes and in situ radical polymerization process. The ionic interactions between CNCC and g-C3 N4 acted as sacrificial bonds enabled highly stretchability of the hydrogel. The hydrogel showed high sensitivity (gauge factor≈5.6, 0–1.6% strain), enabling the detection of human body motion, speech and exhalation. Furthermore, the hydrogel based self-powered device can charge 2.2 μF capacitor up to 15 V from human motion. This multifunctional hydrogel presents potential applications in self-powered wearable electronics. Graphical abstract: Unlabelled Image Highlights: A highly stretchable hydrogel is developed based on nanocomposite incorporation. Cationic nanocellulose (CNCC) is used to disperse/stabilize C3 N4 . The C3 N4 -CNCC endows electrostatic interaction and hydrogen bonding for PAM network. The capabilities of hydrogel as motion and temperature detection are verified. The hydrogel derived self-powered device can charge 47uF capacitor to 15 V.